2010
DOI: 10.1002/jmor.10844
|View full text |Cite
|
Sign up to set email alerts
|

Postembryonic development of Antygomonas incomitata (Kinorhyncha: Cyclorhagida)

Abstract: Postembryonic development in the kinorhynch species Antygomonas incomitata was examined using scanning electron microscopy. The morphology of the six juvenile stages, J-1 to J-6, varies at numerous details, but they can also be distinguished by a few key characters. Juvenile stage 1 by its composition of only nine trunk segments; J-2 by the combination of possessing 10 trunk segments, but no cuspidate spines on segment 9; J-3 by the presence of cuspidate spines on segment 9, but only one pair of cuspidate spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 18 publications
1
23
0
2
Order By: Relevance
“…The identification was based on the presence of two middorsal spines on the terminal segment, as well as the superficial marking of the future division of the terminal segment into segments 10 and 11. These traits were also characteristic for J-3 and J-4 specimens of A. incomitata (Sørensen et al 2010a). The absence of cuspidate spines on segments 4 and 6 (cuspidate spines that otherwise are present in adult specimens) suggests that the specimen more precisely can be identified as J-3, but due to our restricted information about the postembryonic stages in the species, we prefer to consider it as J-3 or J-4.…”
Section: Comparison Of Juvenile Stagesmentioning
confidence: 82%
See 3 more Smart Citations
“…The identification was based on the presence of two middorsal spines on the terminal segment, as well as the superficial marking of the future division of the terminal segment into segments 10 and 11. These traits were also characteristic for J-3 and J-4 specimens of A. incomitata (Sørensen et al 2010a). The absence of cuspidate spines on segments 4 and 6 (cuspidate spines that otherwise are present in adult specimens) suggests that the specimen more precisely can be identified as J-3, but due to our restricted information about the postembryonic stages in the species, we prefer to consider it as J-3 or J-4.…”
Section: Comparison Of Juvenile Stagesmentioning
confidence: 82%
“…In a recent study on the postembryonic development in Antygomonas incomitata several new hypotheses about developmental and evolutionary pathways among cyclorhagid kinorhynchs were proposed (Sørensen et al 2010a). Observations on the development of the mouth cone demonstrated that the outer oral styles in early juvenile stages alternated between larger well-developed and small, rudimentary styles, and it was proposed that retention of this alternation in adult specimens could be a paedomorphic trait.…”
Section: Comparison Of Juvenile Stagesmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the juvenile kinorhynch hatches with 9 segments (or zonites) and gradually increases the number during 5-6 juvenile molts to 13 (Neuhaus 1993(Neuhaus , 1995Sørensen et al 2010 ). No details concerning the changes in the internal organs or organogenesis altogether during the different juvenile stages are known.…”
Section: Postembryonic Developmentmentioning
confidence: 99%